Processes in multiple economic entities = Procesy w wieloczłonowych podmiotach gospodarczych - Sobotkiewicz, Dariusz (Zielona Góra: Faculty of Economics and Management Press)
The article is an attempt at identifying processes carried out in various types of multiple economic entities. It presents a collection of processes which includes basic, supporting and management ones, and which shows the very essence and classification of these.
Keywords: proces; podmiot gospodarczy wieloczłonowy; jednostka nadrzędna; jednostka zależna; process; multiple economic entity; parent unit; subsidiary